Does Financial Innovation Support Development of Pensions and Insurance? The Moderating Role of Green Technology - Kartiko, Nafis Dwi; Mu’min, M. Silahul; Anam, Muhammad Syariful (The International Journal of Financial Systems, 2024)
This study aims to assess the impact of financial innovation on the development of pension and insurance systems in ASEAN countries. Using secondary data analysis methods from 10 ASEAN member countries over the period 2004-2021, this study found that financial innovation has a positive and significant influence on operational efficiency and risk management in both sectors. The adoption of new financial technologies and innovative strategies is proven to promote sustainable growth, as well as strengthen financial stability, which has a positive impact on the welfare of people who depend on pension and insurance services. In addition, the application of green technologies in pension and insurance fund management also supports environmental sustainability and generates positive economic impacts. These findings confirm the importance of policies that support financial innovation as a key strategy in strengthening financial systems in the ASEAN region.